2014
DOI: 10.1128/aac.00095-14
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of the Antimicrobial Peptide OH-CATH30 for Antibiotic-Resistant Pseudomonas aeruginosa Keratitis

Abstract: The therapeutic potential of antimicrobial peptides (AMPs) has been evaluated in many infectious diseases. However, the topical application of AMPs for ocular bacterial infection has not been well investigated. The AMP OH-CATH30, which was identified in the king cobra, exhibits potent antimicrobial activity. In this study, we investigated the therapeutic potential of OH-CATH30 for Pseudomonas aeruginosa keratitis. Ten isolates of P. aeruginosa from individuals with keratitis were susceptible to OH-CATH30 but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Li and coworkers [73] reported that OH-CATH30 is protective in keratitis induced by 10 different antibiotic resistant clinical isolates of pseudomonas. Using a rabbit keratitis model they showed OH-CATH30 itself, or as an adjunctive therapy with levofloxacin, reduced the expression of pro-inflammatory cytokines (TNF-α, IL-1β), leukocyte infiltration, bacterial load and improved disease.…”
Section: Antimicrobial Peptides (Amps) and Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and coworkers [73] reported that OH-CATH30 is protective in keratitis induced by 10 different antibiotic resistant clinical isolates of pseudomonas. Using a rabbit keratitis model they showed OH-CATH30 itself, or as an adjunctive therapy with levofloxacin, reduced the expression of pro-inflammatory cytokines (TNF-α, IL-1β), leukocyte infiltration, bacterial load and improved disease.…”
Section: Antimicrobial Peptides (Amps) and Proteinsmentioning
confidence: 99%
“…Using a rabbit keratitis model they showed OH-CATH30 itself, or as an adjunctive therapy with levofloxacin, reduced the expression of pro-inflammatory cytokines (TNF-α, IL-1β), leukocyte infiltration, bacterial load and improved disease. OH-CATH30 demonstrates an approximately 6 μg/mL MIC for the P. aeruginosa strains tested [73]. …”
Section: Antimicrobial Peptides (Amps) and Proteinsmentioning
confidence: 99%
“…An important site of P. aeruginosa infection is the eye, where these organisms are an important cause of keratitis [34, 35]. A major therapeutic strategy against these biofilm infections is the development of optimized antimicrobial peptides delivered topically [36]. There is substantial interest in the development of more active antimicrobial peptides that could be used topically to treat organisms growing at various anatomical sites, whether in a planktonic or biofilm format.…”
Section: P Aeruginosa Resistance To Antimicrobial Peptidesmentioning
confidence: 99%
“…Our previous work demonstrated that OH30 showed a broad antibacterial spectrum against various bacterial. [12][13][14][15] Moreover, it was reported that OH30 lost approximately 80% antibacterial activity against E. coli 25922 after incubation Figures 3 and 5). In full-thickness wound models, the prepared NP showed significantly fast wound healing and nonscarring results in all the tested groups ( Figure 6).…”
Section: Discussionmentioning
confidence: 93%
“…14 OH30 exhibits an improved clinical effect of treating antibiotic-resistant Pseudomonas aeruginosa that induces rabbit keratitis. 15 Importantly, strong direct bactericidal activity and selective regulation of the expression of various chemokines and cytokines of OH30 are demonstrated to be responsible for protecting the animals from lethal sepsis. 16 Other investigations using reptile cathelicidins as the template also reveal that snake elapid cathelicidins can serve as model molecules for the development of antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%